Increased prevalence of human herpesvirus type 8 (HHV‐8) genome among blood donors from North‐Western Argentina. Issue 3 (31st August 2016) - Hulaniuk, María Laura; Torres, Oscar; Bartoli, Sonia; Fortuny, Lisandro; Burgos Pratx, Leandro; Nuñez, Félix; Salamone, Horacio; Corach, Daniel; Trinks, Julieta; Caputo, Mariela
Abstract : The prevalence of HHV‐8 infection varies widely in South American populations, displaying geographical variations in its distribution. The heterogeneous genetic contributions provided by the transatlantic parental populations that modified the Native American genomes may explain this epidemiological observation. Aiming to determine the prevalence of HHV‐8 genome among healthy South American blood donors and its potential association with genetic ancestry, 772 individuals were screened by a highly sensitive PCR protocol and ancestry was assessed in 414 samples. HHV‐8 DNA was significantly more prevalent among North‐western Argentines than among those from the metropolitan region ( P  = 0.001) and Bolivians ( P  = 0.0008), but no differences were found when compared with Peruvians and Paraguayans. Although significant differences were observed in the ancestry components of the studied populations, no association was found in the genetic admixture between HHV‐8 [+] and HHV‐8 [−] samples from the same place. These results support the hypothesis of the existence of geographical factors related to HHV‐8 prevalence which could be explained by the presence of specific risk factors, cultural characteristics or behaviors, probably related to contaminated saliva and/or sexual transmission. The presence of HHV‐8 in South American blood units available for transfusion and an increased risk of infection in some provinces of North‐western Argentina represent a hazard for immunosuppressed recipients. J. Med. Virol. 89:518–527, 2017 . © 2016 Wiley Periodicals, Inc.